RESPONDING TO COVID-19: INDONESIAN OCCUPATIONAL HEALTH AND SAFETY POLICY FOR CORPORATE COMPLIANCE - Rizaldy Anggriawan (Journal of Industrial Hygiene and Occupational Health, 2020)
The corporate compliance towards the legal policy notably on safety and health of workers becoming a major issue which should be highlighted by the government and entrepreneurs during Covid-19 outbreak in Indonesia. The paper aims to explore the legal framework on occupational health and safety protocols for corporate which were regulated by the government. It highlights the major regulations and policies stipulated by President, ministries, as well as local government such as Governor of DKI Jakarta. It also discovers the penalties or sanctions that will be imposed on companies which infringe the policy. The paper provides the recommendation for the development of current policy practice, in particular for corporate issues in occupational health and safety. The research method used is normative legal research. It reviewed laws, policies, and regulations which should be complied by the corporations in connection with occupational health and safety for workers during the pandemic. The paper found that the government and its subordinate bodies have generally defined an important legal and regulatory framework for the implementation of occupational safety and health for workers. In addition, several existing laws also may provide sanctions and penalties for companies that are still persistent in violating the laws and policies during the spread of the outbreak.Keyword: legal policy; occupational health and safety; corporate, covid-19